Review paperDrug-induced cutaneous vasculitis - Chodorowska, Grażyna; Krasowska, Dorota; Chodorowski, Jakub (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2008)
Drug-induced cutaneous vasculitis belongs to the small vessel vasculitis group. Most frequently, capillaries and post-capillary venules of the superficial vessel dermal plexus are involved. Clinical presentation is polymorphic, but the most characteristic lesions are: palpable purpura, papules, vesicles, blisters, pustules with secondary erosions, ulceration and skin necrosis. Drug-induced vasculitis accounts for about 10-20% of small vessel cutaneous vasculitis cases. Although skin is the primary involved organ, systemic involvement can occasionally be observed, including kidneys, skeletal muscles, and gastrointestinal tract. Many drugs, belonging to various chemical and pharmacological groups of medicines, can cause vasculitis, including antibiotics, insulins, diuretics, NSAIDs, anticonvulsants, sulphonamides, allopurinol, and biologics. For the last several decades, the classification of vasculitides, including cutaneous vessel vasculitis, has remained a matter of controversy. Up till now, attempts have been based on the vessel size or mostly on the histopathological features and are still regarded as a proposed working classification of vasculitis.